2002
DOI: 10.2463/mrms.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of MR Mammography (MRM) in Providing Preoperative Locoregional Information on Breast Cancer: Correlation between MRM and Histological Findings

Abstract: MRM accurately reveals the extent of cancer, including IDS, and is effective at providing preoperative locoregional information for breast-conserving therapy for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…For malignant tumors, they have a relatively high cellular density and therefore will produce a low ADC value in DWI, while for benign lesion, its density is generally low and thus will produce a high ADC value in DWI. Application of DWI in the diagnosis of breast lesions has been reported recently [14,16,22-24]. These studies showed that in malignant breast tumors, the ADC was significantly lower than that in benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For malignant tumors, they have a relatively high cellular density and therefore will produce a low ADC value in DWI, while for benign lesion, its density is generally low and thus will produce a high ADC value in DWI. Application of DWI in the diagnosis of breast lesions has been reported recently [14,16,22-24]. These studies showed that in malignant breast tumors, the ADC was significantly lower than that in benign tumors.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[19][20][21] Moreover, MRM has proven helpful in the diagnosis of intraductal spread of breast cancer. [3][4][5][6][7] In the treatment of breast cancer, breast-conserving therapy is increasingly common and has produced satisfactory results. However, local recurrence is sometimes observed in patients treated with this therapy, and intraductal spread is considered to be one of the risk factors in such recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, importance is also given to the locoregional information of cancer, including intraductal spread. [4][5][6][7] This is because intraductal spread is considered one of the greatest risk factors leading to recurrence following breast-conserving therapy. [8][9][10] Therefore, diagnostic MRM for breast cancer requires not only su‹cient time resolution for diŠerential diagnosis between malignant and benign lesions but also high spatial resolution to reveal small lesions, including intraductal spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with prior studies (Table 1). 1,3,6,[12][13][14][15][16][17][18][19][20][21] Tumour size measured by micro-CT correlated better with histopathological invasive tumour size than any of the three pre-operative imaging modalities. This is likely because micro-CT generates higher resolution images, making fine structures, anatomic features and tumour boundaries more clearly visible.…”
Section: Discussionmentioning
confidence: 99%